Approach to the study of the types of school violence perceived by university students - Nieves Gutiérrez Ángel (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2019)
Bullying is a problem that appears on a daily basis in the educational context, through different stakeholders and forms, which have progressed to newer ways such as cyberbullying and dating violence. The objective of this work is to define and identify the types of school violence that educators in training identify to a greater extent. The method used is of a retrospective and comparative nature, and the sample is made up of 759 educators in training pertaining to the grades of infant education, primary education, and social education. The instruments used are an elaborated "ad hoc" questionnaire and the Revised School Violence Questionnaire (CUVE-R). As main results we found that the type of violence identified to a greater extent refers to the violence of the teaching staff towards the students. Identified to a greater extent by those belonging to the degree of social education, and one who has an experience that oscillates in a period of time between 6 and 12 months.